Advances in asthma: airway inflammation - Busse, William (Henry Stewart Talks, 2012)
Airway inflammation is a complex, interactive, redundant immune response, Components of inflammation in asthma, "Traditional" inflammatory cells in airway inflammation, Mast cells and eosinophils, Lymphocytes, Using monoclonal antibodies to gain insight into the clinical significance of inflammation in asthma, IgE, IL-5, and IL-13, The diversity of patterns of inflammation in asthma, Personalized medicine